Association of endometrial thickness with live birth rates among women undergoing fresh IVF, FET, and PGT cycles - Wenjie Huang; Wenjie Huang; Juan Tang; Juan Tang; Liuyan Wei; Liuyan Wei; Liuying Nong; Liuying Nong; Ni Tang; Ni Tang; Xiaohua Wei; Xiaohua Wei; et al. (Frontiers in Cell and Developmental Biology)
BackgroundEndometrial thickness (EMT) is a crucial indicator of endometrial receptivity in assisted reproductive technology (ART). However, its relationship with pregnancy outcomes remains unclear, especially across different cycle types such as fresh in vitro fertilization-embryo transfer (IVF-ET), frozen-thawed embryo transfer (FET), and preimplantation genetic testing for aneuploidy embryo transfer (PGT-ET). The clinical significance of EMT and its optimal range for improving ART outcomes remain subjects of debate.MethodsThis retrospective cohort study analyzed data from 80,585 ART cycles conducted between July 2008 and December 2022 at a private reproductive center, including 25,683 fresh IVF-ET, 33,112 FET, and 1,071 PGT-ET cycles. EMT was measured via ultrasound on the day of HCG administration and grouped into ranges for comparison. Primary outcomes included live birth rates (LBR) and clinical pregnancy rates (CPR) across EMT ranges. Statistical analyses, including chi-square tests, receiver operating characteristic (ROC) analysis, and adjusted risk ratio (aRR) calculations, were performed to evaluate the association between EMT and pregnancy outcomes.ResultsThe relationship between EMT and LBR was non-linear, with no single cutoff value. LBR varied significantly across EMT ranges, peaking at approximately 12 mm in fresh IVF-ET cycles and around 10 mm in FET and PGT-ET cycles. Higher EMT was generally associated with improved LBR and CPR, but predictive power was limited (AUC: 0.56–0.60). Compared to an EMT of 10–11.9 mm, fresh IVF-ET cycles with EMT <10 mm had significantly lower LBR (aRR: 0.60–0.86), while those with EMT ≥12 mm had higher LBR (aRR: 1.12–1.17). Similar trends were observed in FET and PGT-ET cycles, although sensitivity to EMT variations was lower, particularly in PGT-ET cycles. Miscarriage rates (MR) showed no significant differences across EMT groups.ConclusionThis study demonstrates that EMT has a non-linear association with LBR and CPR across fresh IVF-ET, FET, and PGT-ET cycles, with no single cutoff value. While higher EMT generally correlates with improved outcomes, its overall predictive value for LBR is limited. The findings underscore the need for individualized evaluation of EMT based on cycle type to optimize reproductive outcomes in ART.